Determinan Islamic Social Report Disclosure Industri Barang Konsumsi yang terdaftar di Indeks Saham Syariah Indonesia (ISSI) - Nur Nugrahani Setiawati; Sigid Eko Pramono; Endri (Jurnal Manajemen dan Organisasi, 2019)
This study aims to analyze the influence of company size, muslims on board, women on board, company age, foreign ownership, Islamic securities, profitability, liquidity, leverage against Islamic Social Report disclosures of listed Consumer Goods Industries in Indonesia Sharia Stock Index (ISSI) in 2011-2017. The sample consists of 23 listed Consumer Goods Industries in Indonesia Sharia Index (ISSI) in 2011-2017. Annual reports were analyzed by content analysis method and Panel Data Regression Analysis Model was used to test hypotheses. The analysis shows that company's size, company's age, profitability have a significant positive effect on disclosure of the Islamic Social Report (ISR) in Consumer Goods Industries. Meanwhile, muslims on board, women on board, foreign ownership, Islamic securities, liquidity, leverage have no significant effect towards the disclosure of Islamic Social Report on Consumer Goods Industries.